THE VALIDITY OF INTERACTIVE E-BOOK ON MUTATION TOPIC TO IMPROVE STUDENTS UNDERSTANDING FOR GRADE 12 - Bima Purnama Putra; Lisa Lisdiana (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2023)
The mutation is one of the most challenging topics in Biology for the students since it has abstract concepts. Implementation of interactive learning media, such as interactive e-books, is an option to make mutation topics easier to understand. Unfortunately, the availability of interactive e-books on this topic is still limited. This research aimed to develop an interactive e-book on mutation topics to improve students’ understanding, which is valid for content eligibility, book presentation, and language aspects. The interactive e-book was developed using the Hannafin & Peck model with need analysis, design, and development or implementation phases. The implementation phase was not conducted in the current research. In the development phase, three validators, which included media experts, education experts, and biology teachers, assessed the validity of the developed interactive e-book. Then, data analysis was done using quantitative and qualitative descriptive methods. The result showed that the developed interactive e-book validity was categorized as very high (scored a 93%). Thus, the developed interactive e-book on mutation topics to improve students’ understanding is valid. This research implicates the availability of interactive e-book media to understand mutation topics easier. However, further study to confirm the appropriateness of this interactive e-book implementation is still needed.